Sublobar resection for lung cancer: anatomic or non-anatomic? - Watanabe, Shun-ichi (Video-Assisted Thoracic Surgery, 2017)
The article by Altoki and colleagues (1) published in Journal of Thoracic oncology reported the optimal method of sublobar resection (SR). SR includes anatomic segmentectomy (AS) and wedge resection (WR). Although AS has traditionally been considered superior to WR, there has been no comparative study so far. The objective of their study was to compare oncological outcomes following AS and WR in patients presenting with clinical stage I non-small cell lung cancer. They hypothesized that for cT1N0 non-small cell lung cancer (NSCLC), WR and AS are associated with comparable oncologic outcomes.